1998
DOI: 10.1038/sj.onc.1201487
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a novel actin filament-binding protein from Saccharomyces cerevisiae

Abstract: We puri®ed a novel actin ®lament (F-actin)-binding protein from the soluble fraction of Saccharomyces cerevisiae by successive column chromatographies by use of the 125 I-labeled F-actin blot overlay method. The puri®ed protein showed a minimum M r of about 140 kDa on SDS-polyacrylamide gel electrophoresis and we named it ABP140. A search with the partial amino acid sequences of ABP140 against the Saccharomyces Genome Database revealed that the open reading frame of the ABP140 gene (ABP140) corresponded to YOR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
101
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 26 publications
0
101
0
Order By: Relevance
“…Acetylated Tpm1p then binds to individual actin filaments, stabilizing them and allowing them to become very long. Finally, Sac6p (fimbrin), perhaps aided by Abp140, bundles the filaments together into a cable (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…Acetylated Tpm1p then binds to individual actin filaments, stabilizing them and allowing them to become very long. Finally, Sac6p (fimbrin), perhaps aided by Abp140, bundles the filaments together into a cable (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear why these probes labeled different actin structures within the mouse oocytes, but one possible explanation is that each of these probes could have a preference to somewhat different actin populations, as suggested by several studies [Asakura et al, 1998;Washington and Knecht, 2008;Munsie et al, 2009]. As multiple actin nucleators including formin-2, Spire 1/2 and Arp2/3 are present in meiotic I oocytes, each of which could nucleate a different population of actin filaments in mouse oocytes [Leader et al, 2002;Pfender et al, 2011;Sun et al, 2011].…”
Section: Spindle Migration: Where and How The Force Is Generatedmentioning
confidence: 99%
“…Among them, six showed a partial colocalization with actin bodies (Arc15p, Arc18p, Arc35p, Arp2p, Crn1p, and Srv2p), and five others (Abp1p, Abp140p, Cap1p, Cap2p, and Sac6p) strictly colocalized with actin bodies. Abp1p and Cap1p/ Cap2p are ABPs detected only in actin patches (Drubin et al, 1988;Amatruda and Cooper, 1992;Doyle and Botstein, 1996;Waddle et al, 1996), Abp140p is a protein preferentially found in actin cables (Asakura et al, 1998;Yang and Pon, 2002), and Sac6p has been detected in both actin cables and patches (Drubin et al, 1988;Doyle and Botstein, 1996). To confirm those results and increase when necessary the GFP signal in quiescent cells, 3xGFP fusion proteins were constructed and shown to be functional (see Materials and Methods).…”
Section: Several Actin-binding Proteins Colocalize With Actin Bodiesmentioning
confidence: 99%